Biological and Chemical Studies of Essential Oil and Extracts of Rhizome of Acorus calamus Linn - Timilsina, Rajesh; Tandukar, Pooja; Pathak, Ishwor (Journal of Nepal Chemical Society, 2022)
The essential oil (EO) of the rhizome of Acorus calamus Linn. was isolated by using a Clevenger apparatus and extracts were prepared by cold percolation technique using the solvents hexane and methane. The chemical constituents of EO were analyzed by Gas Chromatography-Mass Spectroscopy (GC-MS) analysis. A total number of nine chemical compounds were identified and quantified occupying 100% of the total oil composition. The major chemical constituent was reported to be β-asarone (84.87%). Acid value, saponification value, and iodine number of the oil were measured and found to be 0.24 mg KOH/g, 0.42 mg KOH/g, and 31.75 g I2/100gm,  respectively. The antibacterial activity of the hexane and methanol extract was examined against two bacteria by the agar well diffusion method. The hexane extract showed antibacterial activity against E. coli with a zone of inhibition(ZOI)of 10 mm, and. subtilis with ZOI of 7 mm. The methanol extract showed antibacterial activity against B. subtilis only, with a ZOI of 4 mm. Hexane and methanol extract also showed significant antifungal activity against fungi C. albicans with a ZOI of 6 mm and 5 mm, respectively.DPPH assay showed that the percentage of free radical scavenging activity increased with an increase in the concentration of the extract. The total phenolic content of the methanol extract of A. calamus was found to be 48.36 mg/g GAE.